New Synthesis, Structure and Analgesic Properties of Methyl 1-R-4-Methyl-2,2-Dioxo-1H-2λ6,1-Benzothiazine-3-Carboxylates - Liliana Azotla-Cruz; Irina V. Lijanova; Igor V. Ukrainets; Natalya V. Likhanova; Octavio Olivares-Xometl; Natalya L. Bereznyakova (MDPI AG, 2017)
According to the principles of the methodology of bioisosteric replacements a series of methyl 1-R-4-methyl-2,2-dioxo-1H-2λ6,1-benzothiazine-3-carboxylates has been obtained as potential analgesics. In addition, a fundamentally new strategy for the synthesis of compounds of this chemical class involving the introduction of N-alkyl substituent at the final stage in 2,1-benzothiazine nucleus already formed has been proposed. Using nuclear magnetic resonance (NMR) spectroscopy, mass spectrometry and X-ray diffraction analysis it has been proven that in the DMSO/K2CO3 system the reaction of methyl 4-methyl-2,2-dioxo-1H-2λ6,1-benzothiazine-3-carboxylate and alkyl halides leads to formation of N-substituted derivatives with good yields regardless of the structure of the alkylating agent. The peculiarities of NMR (1Н and 13С) spectra of the compounds synthesized, their mass spectrometric behavior and the spatial structure are discussed. In N-benzyl derivative the ability to form a monosolvate with methanol has been found. According to the results of the pharmacological testing conducted on the model of the thermal tail-flick it has been determined that replacement of 4-ОН-group in methyl 1-R-4-hydroxy-2,2-dioxo-1H-2λ6,1-benzothiazine-3-carboxylates for the methyl group is actually bioisosteric since all methyl 1-R-4-methyl-2,2-dioxo-1H-2λ6,1-benzothiazine-3-carboxylates synthesized demonstrated a statistically significant analgesic effect. The majority of the substances can inhibit the thermal pain response much more effective than piroxicam in the same dose. Under the same conditions as an analgesic the N-methyl-substituted analog exceeds not only piroxicam, but more active meloxicam as well. Therefore, it deserves in-depth biological studies on other experimental models.